BERBAGAI JENIS NEAR-RING DAN KETERKAITANNYA - Pranadita Sitaresmi (MATEMATIKA FSM, UNDIP, 2016)
Let be a non empty set with two binary operations, those are additive and multiplicative. Triple is near-ring if is a group structure toward additive operation, semigroup structure toward multiplicative operation and statisfied right distributive law toward that both binary operation. is said to be regular if for every there exists such that . If is a group is called a near field. Near ring is said to be near ring if for every there exists such that and said to be near ring if for every there exists such that . Futhermore, disscussed the relation between near ring and near ring with regular near ring and near field. Every near field are , near ring. Every regular near ring is an near ring and if is weak commutative then is an near ring.